Estilos de aprendizaje y su -relación con el rendimiento académico, en el: área de idioma extranjero - Inglés, en los estudiantes del 5°grado de educación secundaria de la I.E. "Elsa Perea Flores" de la ciudad de Tarapoto, en el año 2009 - Vasquez Caro, Edwar (2009)
The research entitled "Learning styles and their relationship to academic achievement in the field of foreign language - English, students in the 5th grade of secondary education in the 1.E. "Elsa Perea Flores" District of Tarapoto, in the year 2008", aimed to determine the relationship between learning styles and academic performance in the field of foreign language - English, students in the 5th grade of Secondary Education the "Elsa Perea Flores" District of Tarapoto, in 2008. The investigation was based on the taxonomy of Learning Styles of Kolb, who provides four styles: active, thoughtful, pragmatic and theoretical. On the basis of which has been hypothesize that learning styles are related significantly with academic achievement in the field of foreign language - English, students in the 5th grade of secondary education in the l. E. "Elsa Perea Flores" District of Tarapoto, in 2008. The sample consisted of 45 students, who had administered a learning style questionnaire and collected their academic performance through the records of notes corresponding to the quarters 1 and 11 of the school year 2008. Processing the data has found it possible to establish that there is direct relationship between the weak learning styles active, thoughtful and pragmatic approach to academic progress, while the inverse relationship is between the style of theoretical learning with academic performance. Besides the relationship between learning styles active, thoughtful, theoretical and pragmatic academic performance is not significant.